Quantifying the Utility of a Multidisciplinary Neuro-oncology Tumor Board. (16th November 2020) - Khalafallah, Adham M; Jimenez, Adrian; Romo, Carlos; Kamson, David; Kleinberg, Lawrence; Weingart, Jon; Brem, Henry; Grossman, Stuart; Mukherjee, Debraj
Abstract: INTRODUCTION: There is limited research attempting to measure the efficacy of tumor boards (MDTBs) in the treatment of patients with tumors affecting the nervous system. METHODS: A prospective study of patients discussed at four hospitals' MDTB between July and November 2019 was performed. Demographic data, diagnoses, treatment plans, and eligibility for clinical trials were recorded, among other variables. RESULTS: A total of 176 cases met eligibility criteria. The majority (53%) were male with a mean age of 52 years old. The most frequent diagnosis was glioblastoma (32.4%). Among the evaluable cases, MDTBs led to 38 (21.6%) changes in image interpretation and 103 (58.2%) changes in patient management. Additionally, patients whose cases were discussed at MDTBs had significantly shorter referral times compared to patients who were not discussed (p = .024). CONCLUSION: MDTB discussions led to a significant number of diagnostic and treatment plan changes as well as shortened referral times, highlighting the potential clinical impact of multidisciplinary care for patients with nervous system tumors.